AB0727 Increased Rates of Hypertension in Patients with Psoriatic Arthritis Compared To Psoriasis Alone: Results from The UK Biobank. (15th July 2016) - Bellou, E.; Verstappen, S.M.M.; Cook, M.; Sergeant, J.C.; Warren, R.B.; Barton, A.; Bowes, J.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic inflammatory arthritis associated with the presence of psoriasis. Lifestyle factors such as body mass index (BMI), smoking and alcohol consumption have been reported to contribute to the risk of both diseases. These risk factors also contribute to cardiovascular disease (CVD) which is a major cause of morbidity and mortality in patients with psoriasis and PsA. Objectives: To compare lifestyle factors between individuals with PsA, psoriasis and a control group and to assess the association between these inflammatory diseases and CVD outcomes utilising the UK Biobank resource. Methods: UK Biobank recruited 502, 664 people aged 40–70 years in the UK between 2006 and 2010. Data on lifestyle, sociodemographics, health and medical history were collected at the assessment visit by questionnaire and interview by research nurse. Participants were asked if they have ever been diagnosed by a physician with a disease. Lifestyle factors including alcohol (current or past drinker) and smoking status (ever or never) were recorded and height and weight measured to calculate BMI. In this cross-sectional study, the frequency of these factors was compared between PsA, psoriasis and healthy controls using logistic or linear regression analyses depending on the outcome, adjusting for age and gender. Comparison between disease groups was performed by linear combinations of coefficients post estimation. Three CVD outcomes: heart attack, angina and hypertension, were tested for association with disease group using logistic regression including BMI, smoking, alcohol, age and sex as covariates. Odds ratios (OR) and β coefficients are reported with 95% confidence intervals (CI). Results: 862 people with PsA, 4, 761 with psoriasis and 465, 371 control participants were included in the study (Table). Compared to the control group; both the PsA and psoriasis groups had higher BMI (β 1.43 (95% CI 1.11:1.75) and 0.72 (0.58:0.85) respectively), the psoriasis group smoked more (OR 1.63 (1.54:1.72)) and patients with PsA were less likely to be current drinkers (OR 0.68 (0.55:0.85)). Compared to patients with psoriasis, patients with PsA had higher BMI (β 0.69 (0.32:1.06)) and were less likely to be ever smokers and current drinkers (OR 0.70 (0.61:0.81) and 0.65 (0.51:0.83), respectively). Finally, hypertension was more prevalent in PsA compared to the control and psoriasis cohorts (OR 1.71 (1.48:1.97) and 1.55 (1.33:1.82), respectively). Conclusions: Using a large population based cohort we show that self-reported CVD outcomes, in particular hypertension, are significantly higher in PsA compared to psoriasis independently of known CVD risk factors. The results contribute to our understanding of the lower quality of life reported by patients with PsA. Disclosure of Interest: None declared